A novel 3 -D printed wrist powered upper limb prosthesis using whippletree mechanism - Kumarage, K.P.L.; Wickramarathan, W.H.S.; Madhushan, V.; Mugilgeethan, V.; Neethan, R.; Thanihaichelvan, T. (The Institution of Engineers, Sri Lanka, 2019)
This study focuses on the development of a 3-D printed low-cost novel solution for upper limb amputees in Sri Lanka. Prosthetic devices available in Sri Lanka are declined by most patients with trans-metacarpal amputation due to the high cost and discomfort. Worldwide the 3-D printing technology has been recognized as a convenient solution for prostheses owing to its customizability and low cost. The adaptive grasp functionality in mechanical prostheses is important to effectively utilize the limited angle of the wrist. Wrist motion of healthy individuals and the limitations in wrist flexion occurring after amputation were studied. With the findings, a novel design was developed incorporating a modified whippletree mechanism. The prosthesis was printed and tested for adaptive grasp and comfort. In this testing, whippletree mechanism was used to improve the adaptive grasp through proper force distribution and a flexible material was introduced for wearable comfort. It was found that this kind of prosthetic hands will help the amputee to grasp complex shaped objects while providing good comfort.
Keywords: Trans-Metacarpal amputation; 3-D printing; Adaptive grasp; Whippletree mechanism